2022
DOI: 10.1038/s41467-022-34493-1
|View full text |Cite
|
Sign up to set email alerts
|

Base-editing-mediated dissection of a γ-globin cis-regulatory element for the therapeutic reactivation of fetal hemoglobin expression

Abstract: Sickle cell disease and β-thalassemia affect the production of the adult β-hemoglobin chain. The clinical severity is lessened by mutations that cause fetal γ-globin expression in adult life (i.e., the hereditary persistence of fetal hemoglobin). Mutations clustering ~200 nucleotides upstream of the HBG transcriptional start sites either reduce binding of the LRF repressor or recruit the KLF1 activator. Here, we use base editing to generate a variety of mutations in the −200 region of the HBG promoters, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 77 publications
(102 reference statements)
0
22
0
1
Order By: Relevance
“…Importantly, Zeng et al , suggested that two rounds of electroporation were required to achieve high editing efficiencies by using the A3A (N57Q)-BE3 editor as RNP complex with a sgRNA targeting the +58 BCL11A erythroid enhancer ( Zeng et al, 2020 ). However, in this study and in a recent study by Antoniou et al , it is suggested that one mRNA-based nucleofection of BEs is adequate to reach high efficiencies in HSPCs ( Antoniou et al, 2022 ). Furthermore, deconvolution of sequence traces did not show any edits outside the predicted editing window (position 4–8 of sgRNA) for BCL11A and HBG as targets, and only the intended transition events (C>T) and no transversion events (C>A, C>G) were detected above background.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Importantly, Zeng et al , suggested that two rounds of electroporation were required to achieve high editing efficiencies by using the A3A (N57Q)-BE3 editor as RNP complex with a sgRNA targeting the +58 BCL11A erythroid enhancer ( Zeng et al, 2020 ). However, in this study and in a recent study by Antoniou et al , it is suggested that one mRNA-based nucleofection of BEs is adequate to reach high efficiencies in HSPCs ( Antoniou et al, 2022 ). Furthermore, deconvolution of sequence traces did not show any edits outside the predicted editing window (position 4–8 of sgRNA) for BCL11A and HBG as targets, and only the intended transition events (C>T) and no transversion events (C>A, C>G) were detected above background.…”
Section: Discussionmentioning
confidence: 46%
“…By contrast, mRNA- or mRNA/gRNA-based delivery offer near-universal applicability, high speed of adoption and application, low toxicity and high editing efficiencies. For the example of hemoglobinopathies, a growing body of work demonstrates that delivery of in vitro transcribed genome editing tools, such as BEs and TALENs in sickle-cell-disease and β-thalassemic cells, achieved high levels of functional correction and reached high editing efficiencies (40%–80%) ( Patsali et al, 2019b ; Gaudelli et al, 2020 ; Newby et al, 2021 ; Antoniou et al, 2022 ). Depending on the setup, mRNA-based delivery might vastly outperform editing efficiency achieved by RNPs for BEs ( Newby et al, 2021 ), while potentially modulating viral and immune transcriptional signatures and overall reducing DNA-damage, cell-cycle and metabolic response pathways in HSPCs ( Cromer et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human CD45 + cells were differentiated into mature RBCs using a three-phase erythroid differentiation protocol 51,52 .…”
Section: Ex Vivo Erythroid Differentiation Of Human Cd45 + Cellsmentioning
confidence: 99%
“…Because single-strand nicks are repaired by the high-fidelity base-excision repair pathway, BEs have been claimed to reduce on-target and off-target effects ( 36 ). However, recent data demonstrated deletion of a 4.9 kb region after base editing of the HBG1/HBG2 promoters, indicating that also base editing can induce structural variations ( 76 ). Furthermore, bystander editing effects ( 77 ) and gRNA-independent off-target activities on both DNA and RNA ( 78 , 79 ) have been described for both ABEs and CBEs.…”
Section: Off-target Effectsmentioning
confidence: 99%